Effectiveness of Remote High-Intensity Aerobic Interval Training on Quality of Life and Physical Health in Breast Cancer Survivors: Two Years Follow-Up - Aija Klavina PhD; Sintija Liepina MS; Maija Viskinte; Edgars Bernans PhD (Integrative Cancer Therapies, 2025)
This study aimed to evaluate the long-term effects of a remotely supervised HIIT program implemented during six months NACT on quality of life (QoL) and physical health outcomes in women with breast cancer, assessed 18–24 months post-intervention. The HIIT intervention study was two arm randomized control trial implementing remotely supervised 4x4 min training at an intensity of 85-95% of peak heart rate for 6 months during NACT. Physical health was assessed by treadmill VO 2peak , 6MWT and sit-to-stand test, and QoL by the EORTC QoL30. Participants were 24 BC survivors who agreed to participate in follow-up 18-24 months after the intervention (HIIT= 13, CG = 11). Results: At follow-up, the HIIT group demonstrated significant difference in change of VO 2peak (p = .046, ES = .169) and time to exhaustion (p = .024, ES= .211). Both groups presented significantly higher 6MWT and sit to stand test results at follow-up compared to pre-NACT (p < .05), while the magnitude of change was not significant. HIIT group results demonstrated moderate associations between 6MWT and Physical Functioning (r = −.674, p = .012) and Emotional Functioning (− .567, p = .043). A remotely supervised 6-months HIIT during NACT showed positive effects on submaximal cardiorespiratory fitness, absolute VO 2peak and muscle strength at 18-24 months follow-up. Moderate negative association between 6MWT and perceived physical and emotional functioning highlighted the complex relationship between physiological outcomes and self-reported QoL. The HIIT can be recommended during NACT to maintain prolonged effects on physical health of BC survivors.